Integration of Renewable Energy, Microgrids, and EV Charging Infrastructure: Challenges and Solutions - Prianka, Yingking Mitra; Sharma, Anik; Biswas, Chanchal (Peneliti Teknologi Teknik Indonesia, 2024)
As global efforts toward sustainable energy transition and electric vehicle (EV) adoption accelerate, the seamless integration of renewable energy sources (RES), microgrids, and EV charging infrastructure is becoming increasingly critical. This review examines recent advancements in the integration of solar and wind power with microgrids and EV charging infrastructure, focusing on energy management techniques, grid stability solutions, and the development of charging infrastructure. The study emphasizes the difficulties relating to energy management techniques, grid stability, intermittency and variability of renewable energy, and the development of charging infrastructure. Microgrids are critically examined for their ability to enhance energy security and resilience by integrating distributed energy resources (DERs) and optimizing power generation and usage. The contribution of microgrids to improving energy security and resilience is thoroughly examined, along with how they allow distributed energy resources (DERs) to maximize power generation and consumption. Additionally, this review assesses how energy storage systems (ESS) and bidirectional vehicle-to-grid (V2G) technology affect peak load reduction and energy balance. The integration of these systems is made easier by a number of smart grid technologies, power electronics solutions, and communication protocols that are covered. The assessment also discusses the standards, policy frameworks, and future lines of inquiry that will be needed to hasten the establishment of a reliable and scalable network of electric vehicle charging stations coupled with microgrids and renewable energy sources. The results of this research offer valuable perspectives for creating sustainable energy strategies that facilitate the swift expansion of electric vehicle adoption, all the while reducing ecological footprints and augmenting grid stability.